The effect of visual teaching method using PowerPoint, video and photo based on educational management model on conceptual learning - ebrahim khashi jamalzehi (Institute of Management fekrenoandish, 2021)
The aim of this study was how to determine the effectiveness of visual teaching method using PowerPoint, video and photos and based on the educational management model on students' conceptual learning. A quasi-experimental method was used in this study. The statistical population included female students of humanities in districts 1 and 2 of Tehran who were studying in the academic year 2017-2018. The sample size was determined based on Krejcie Morgan table, according which 297 students from among 1300 female students studying in the field of humanities. The education management model was based on visual instruction in the history course for the experimental group, and the current and traditional teaching method for the control group. The students' pre-knowledge was measured by means of the academic achievement test of the history course regarding the current situation at the first step, and after implementing the model for the experimental group, post-test was performed in either groups. The data collected from the paired t-test showed a significant effect of the educational management model based on visual teaching on conceptual learning of students' history course in the experimental group. With the familiarity and support of school principals, it is necessary to create a suitable structure and atmosphere for the implementation of the learner management model in the teaching process.t-test showed a significant effect of the educational management model based on visual teaching on conceptual learning in the history of students in the experimental group. It is necessary to create a suitable structure and atmosphere for the implementation of the learner management model in the teaching process through familiarizing and support of school principals.